Polymeric precursor method to the synthesis of XWO(4) (X = Ca and Sr) thin films-Structural, microstructural and spectroscopic investigations - Pontes, Fenelon Martinho Lima [UNESP]; Galhiane, Mario Sergio [UNESP]; Santos, L. S. [UNESP]; Petit, L. A. [UNESP]; Kataoka, F. P. [UNESP]; Mabuchi, G. H. [UNESP]; Longo, Elson [UNESP]; Zampieri, M.; Pizani, P. S. (Elsevier B.V. Sa, 2009)
Stoichiometric XWO(4) (X = Ca, and Sr) thin films were synthesized using the polymeric precursor method. In this soft chemical method, soluble precursors such as strontium carbonate, calcium carbonate and tungstic acid, as starting materials, were mixed in an aqueous solution. Through the polyesterification reaction, evidences of the formation of the W-citrate complex and the strontium were obtained by (13)C NMR and FT-Raman spectroscopy. The thin films were deposited on silicon and platinum-coated silicon substrates through the spinning technique. The surface morphology and crystal structure of the thin films were investigated using atomic force microscopy (AFM), X-ray diffraction (XRD), specular reflectance infrared Fourier transform spectroscopy, and micro-Raman spectroscopy. Nucleation stages and surface morphology evolution of the thin films on silicon substrates were studied by atomic force microscopy. X-ray diffraction characterization of these films showed that the XWO(4) (X = Ca, and Sr) thin film phases crystallize at 500 degrees C from an inorganic amorphous phase, given that no intermediate crystalline phase was identified. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Thin films; Chemical synthesis; X-ray diffraction